Jamaat Tablighi and negotiation of identity in the global world - Ma'mun, Sukron; Chairul Huda, Muhamad; Muhsin, Ilyya; Maifizar, Arfriani; Muhammad, Zikri (Opción, 2020)
The study aims to investigate Jamaat Tablighi and Negotiation of Identity in the global world. The literature study here is an analysis of the study focus above based on related literature data from various sources on Jamaat Tablighi. As a result, some events of Jamaat Tablighi bring together Tablighis around the world to become a field that unites the idea and concept of Tablighis comprehensively. In conclusion, Jamaat Tablighi identifies themselves as a Sufism-Islamic-traditional revivalist movement. By the identity, Jamaat Tablighi comes through barriers of global communities and it becomes the most successful of Islamic transnational movement.